Violent Intimacies: Women and White Supremacy in Imperial Intimacies and The Woman of Colour - Sinanan, Kerry (Romanticism on the Net, 2024)
Reading The Woman of Colour (1808) and Hazel Carby’s Imperial Intimacies: A Tale of Two Islands (2019) together, this essay examines how both texts reveal the chasm between Black mothers and women and white mothers and women within racial capitalism. Abolitionist sentiment and white feminism posit a universal feminism that Carby and The Woman of Colour reveal to be exclusionary to women of colour. Imperial Intimacies and The Woman of Colour explicitly expose the domestic as a site of violent intimacy that is perpetrated on Black and Brown women by their white women relatives: far from the supposed thrust of feminist abolition, white women’s sympathies in both texts end at the hearth and home, and the violence of the racist state is repeated by them in the domestic sphere.